2020
DOI: 10.1088/1757-899x/921/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of mechanisms of formation of corrosive aggressiveness of soils and grounds of underground gas pipeline routes and on its basis assessment of service life of gas pipes in various soil-climatic zones

Abstract: The experience of studying the problem of corrosive aggressiveness of soils and grounds in terms of improving the reliability of Gazprom’s pipeline systems operation is summarized and presented. Soil factors causing surface corrosion of gas pipelines in soil conditions are studied. Based on the obtained results, it was suggested to evaluate not only the corrosive aggressiveness of soils and the gas pipe lifetime, but also the corrosive resistance of pipe metal in corrosive environments. Special attention is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the other hand, the obtained chemical, physicochemical and biological characteristics of the corrosion aggressiveness of soils and grounds did not provide reliable information for the development of technology to increase the service life within a certain soil-climatic zone. Application of the results obtained for a different soil-climatic zone does not lead to the desired result, as evidenced by numerous data [1]. However, it has been shown that the intensity of corrosion process development is largely determined by the temperature conditions of the soil and the temperature of the pumped gas.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the obtained chemical, physicochemical and biological characteristics of the corrosion aggressiveness of soils and grounds did not provide reliable information for the development of technology to increase the service life within a certain soil-climatic zone. Application of the results obtained for a different soil-climatic zone does not lead to the desired result, as evidenced by numerous data [1]. However, it has been shown that the intensity of corrosion process development is largely determined by the temperature conditions of the soil and the temperature of the pumped gas.…”
Section: Introductionmentioning
confidence: 99%